Beachside bed and breakfast - Ramsay, Hope (Ramsay, Hope. Moonlight Bay series, 2022)
Ashley Howland Scott has no time for romance as she grieves the loss of her husband, cares for her young son, and runs Magnolia Harbor's only bed and breakfast. Ashley never imagined she'd notice--let alone have feelings for--another man after her husband was killed in Afghanistan five years earlier. But slowly, softly, Rev. Micah St. Pierre has become a friend...and now maybe something more. Despite her reluctance, Ashley has to admit that Micah is kind, thoughtful, and handsome to boot. All the more reason to steer clear of him. She can't risk her heart again. After becoming the center of Magnolia Harbor's rumor mill once, Micah St. Pierre has no interest in letting the members of the local quilting club play matchmaker for him. Besides, the only woman he's interested in is the one he can never have. Micah is not allowed to date a member of his congregation, so there's no point in sharing his feelings with Ashley, no matter how much he yearns to. But the more time they spend with each other, the more Micah wonders whether Ashley is his match made in heaven.--